Post- Yolanda rapid assessment in natural and planted plots in Maliwaliw Island, Salcedo Eastern Samar. - Esmeña, Ronnie P.; dela Cruz, Margarita (Ronnie P. Esmeña, 2014)
This study reports on the rapid assessment conducted to assess the condition of the mangroves after Typhoon Haiyan (Yolanda). Two sampling sites were established: one in the planted and the other in natural area and the physico-chemical parameters of each sampling site were noted at the conduct of the study. Field sampling was carried out once a month from February to April. Species composition, degree of damage, recovery and regenerative capacity of the mangrove stand was evaluated in situ. Species such as B. gymnorhizza, R. stylosa, R. apiculata and S. alba were observed in the natural site whereas the planted site is mainly comprised by Rhizophora species. The natural mangrove stand was relatively more diverse compared to the planted plots. High percentage of damage (60.67%) was seen in the planted plots compared to the natural areas having only 5.13%. Overall densities of saplings and seedlings in both planted and natural plots of mangroves exhibited an increasing trend. Hence, the overall status of the mangroves is not vulnerable.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.